PENGARUH STRATEGI SCAFFOLDING TERHADAP KEMAMPUAN PEMAHAMAN MATEMATIS SISWA SEKOLAH DASAR - Rismawati Rismawati; Hany Handayani (Jurnal Silogisme : Kajian Ilmu Matematika dan Pembelajarannya, 2018)
Scaffolding is a learning strategy that is used in learning by providing assistance to taste to students based on the difficulties experienced by students. The purpose of this research is to know the influence of scaffolding strategies against the ability of mathematical understanding of grade III SD in Purwakarta. This research uses a quantitative approach with quasi experimental research methods and research designs The Nonequivalent Control Group Design with techniques of sampling Non Probability Sampling the sampling type is saturated. The object of this research is the whole grade 3 SD 2017/2018 school year with a total of 48 students (Male = 23, female = 25). Data collection techniques in the study using this type of test in the form of sheets of matter and types of the non test in the form of observation and documentation. Data analysis in this study uses the construction and validity testing of the validity of the content. The results showed there is the influence of the use of scaffolding strategies against the mathematical understanding of the capabilities of the students. This calculation results obtained from test-t with P-Value calculation results (Sig 2-tailed) for 0.000 which means less than 0.05 significant level. The earnings results of the pretest average score at 29.92 while IE experiment class results average value of experimental class posttest was 73.92. Then for obtaining the value of an average pretest classes control i.e. 30.96 while the average value of posttestnya was 55.17. The use of scaffolding strategies can be used by subsequent researchers to conduct research in the subject matter, having regard to the appropriations used and skills of teachers in the conditioning classes, to obtain maximum results.